2011
DOI: 10.5455/jeim.250411.or.007
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of vascular reactivity at different time-course on streptozotocin-induced diabetic rats

Abstract: Objective: Impairment of vascular reactivity in diabetes may be due to endothelium and/or vascular smooth muscle dysfunction. This study aimed to verify the role of endothelium and vascular smooth muscle in diabetes at different time-course after streptozotocin (STZ) administration.Method: Endothelium-intact and denuded aortic rings obtained from non-diabetic and diabetic rats at different time-course (1-4 weeks) were subjected to graded concentrations of potassium chloride (KCl) and phenylephrine (PE), L-NAME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…As PDPN follows a progressive course, vascular deterioration and nerve degeneration become increasingly important in a chronic stage of PDPN (Partanen et al, 1995;Al-Delaimy et al, 2004;Litwak et al, 2013). In line with clinical observations, experimental work has demonstrated that pathophysiological changes in streptozotocin-induced diabetic rats are progressive as well (Wei et al, 2003;Hassan et al, 2011). As SCS mediated vasodilation is CGRP receptor dependent, the potential benefit from improving blood flow might become apparent when receptor-dependent vascular reactivity is affected over a longer period of time.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…As PDPN follows a progressive course, vascular deterioration and nerve degeneration become increasingly important in a chronic stage of PDPN (Partanen et al, 1995;Al-Delaimy et al, 2004;Litwak et al, 2013). In line with clinical observations, experimental work has demonstrated that pathophysiological changes in streptozotocin-induced diabetic rats are progressive as well (Wei et al, 2003;Hassan et al, 2011). As SCS mediated vasodilation is CGRP receptor dependent, the potential benefit from improving blood flow might become apparent when receptor-dependent vascular reactivity is affected over a longer period of time.…”
Section: Introductionmentioning
confidence: 85%
“…CON-SCS has been shown to increase peripheral blood perfusion in the acute phase of streptozotocin induced diabetic rats (Wu et al, 2007;Gao et al, 2010). Peripheral blood perfusion, in addition to structural micro-and macrovascular abnormalities, is impaired especially in the chronic diabetic condition (Orchard et al, 1990;Tesfamariam et al, 1991;Creager et al, 2003;Wei et al, 2003;Cade, 2008;Hassan et al, 2011). A small prospective open-label study in PDPN patients failed to demonstrate a significant effect of CON-SCS on microcirculatory function, whereas these patients did experience pain relief (de Vos et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…2007), unchanged endothelium‐independent relaxation (Cameron & Cotter 1992), and increased (Taylor et al. 1994) or decreased (Hassan et al. 2011) contraction response to phenylephrine (PE).…”
mentioning
confidence: 99%
“…Diabetes, either in human or animals, is associated with a number of changes in the cardiovascular system. Animal models of diabetes are associated with the impairment of endothelium-dependent relaxation (Matsumoto et al 2007), unchanged endothelium-independent relaxation (Cameron & Cotter 1992), and increased (Taylor et al 1994) or decreased (Hassan et al 2011) contraction response to phen-ylephrine (PE). Moreover, human type 2 diabetes is associated with decreased basal and stimulated release of nitric oxide (NO) (Woodman et al 2006).…”
mentioning
confidence: 99%